Technology-Based Companies: The Case of South American Countries - Morales-Molina, Tania (2022)
In recent decades, technology-based companies have achieved significant global recognition, given their importance and substantial contribution to the economic and sustainable development of organizations and society at large, through job and wealth creation. The research objective focuses on determining the relationship between technology-based companies and R&D and innovation spending. To meet the objective, the methodology applied was based on the application of Pearson’s correlation coefficient statistical technique, since it allows to obtain an association coefficient between variables that do not behave normally. The results indicate that R&D spending and innovation are representative factors for the operation of technology-based companies.